Design and fabrication of an economical coconut Dehusking machine - R, Krishnan; P.P, Mahalingam; Ratna kumar.P.S, Samuel; T, Babu (International Journal of Engineering and Technology, 2018)
A coconut is the fruit of a coconut palm belonging to arecaceae family and it is used by one third of the population in the world. The coconut needs to be dehusked before it could be utilized for any of the purpose it serves. The husk of the coconut can be removed by various techniques. Manual dehusking is the conventional process followed widely among farmers. The labour cost incurred and the time consumed can be considerably decreased by increasing the usage of machines. All the coconut growers cannot afford to own an automated machines used in developed countries because of high cost. This project attempts in making a dehusker which is affordable and also has higher productivity. The cost of the dehusking machine is also affordable which makes it better than hydraulic dehusking machine. The machine has two rotating shafts with spikes mounted on a frame. The shafts are rotated by a three phase motor. The output speed is reduced to 30 rpm by using gear box. When the coconut is placed between the spiked shafts rotating in opposite directions, the husk is peeled off from the coconut.
Keywords: Dehusking; Machine; Affordable; Productivity